2006
DOI: 10.1063/1.2349299
|View full text |Cite
|
Sign up to set email alerts
|

Tunable threshold voltage and flatband voltage in pentacene field effect transistors

Abstract: Charged interface states are introduced by UV-ozone treatment of a polymer gate dielectric, parylene, prior to deposition of the organic semiconductor, pentacene, thereby modifying the organic field effect transistor (OFET) operation from enhancement to depletion mode. Quasistatic capacitance-voltage measurements and the corresponding current-voltage characteristics show that the threshold voltage VT and flatband voltage VFB can be shifted by over +50V, depending on the ozone exposure time. This work demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 11 publications
3
44
0
Order By: Relevance
“…The results are consistent with other reports, and a plausible explanation is that UV treatment creates excess negatively charged sites on the pentacene/PMMA interface. 6,7 Accordingly, the S.S. was enlarged and the V th positively shifted. However, the linear field-effect mobility ͑ FET ͒ was not affected by UV treatment and was about 0.1 cm 2 /V s for both devices.…”
Section: Resultsmentioning
confidence: 97%
“…The results are consistent with other reports, and a plausible explanation is that UV treatment creates excess negatively charged sites on the pentacene/PMMA interface. 6,7 Accordingly, the S.S. was enlarged and the V th positively shifted. However, the linear field-effect mobility ͑ FET ͒ was not affected by UV treatment and was about 0.1 cm 2 /V s for both devices.…”
Section: Resultsmentioning
confidence: 97%
“…28 The oxygen plasma treatment instead of UV-ozone assisted reactions may further roughen the surface in comparison. Since parylene is known to degrade under UV irradiation, the plasma approach may be more gentle, since the UV degradation weakens the dielectric properties of parylene.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3͔ displayed a significant gate hysteresis before and after passivation between forward ͑V GF ͒ and backward ͑V GB ͒ sweeps of the gate voltage. This phenomenon is often observed in CNT based transistors, and it is attributed to charge injection from nanotube at large gate voltages, 14 water molecules, 5 trapped charges at parylene-SWNT interface, 15 other trapped charges from solution processed CNTs 16 ͑e.g., surfactant, ionic molecules, etc.͒ and contamination originating during the fabrication of the device. 16 Prior to the deposition of the source and drain electrodes, the parylene-C surface was roughened in an oxygen plasma to improve the adhesion of chromium/ gold electrodes.…”
Section: Applied Physics Letters 97 153120 ͑2010͒mentioning
confidence: 99%
“…This oxygen plasma treatment breaks the bonds on the parylene surface and induces fixed and mobile charges at the parylene-SWNT interface which can create hysteresis in the CNT FETs. 15 Furthermore, DEP assembly was conducted using nanotubes suspended in deionized water, and both assembly and the I-V study were conducted in atmospheric conditions which all contribute to the observed hysteresis before encapsulation.…”
Section: Applied Physics Letters 97 153120 ͑2010͒mentioning
confidence: 99%